Epidemiology of MRSA CC398 in hospitals located in Spanish regions with different pig-farming densities: a multicentre study. (16th May 2019) - Ceballos, Sara; Aspiroz, Carmen; Ruiz-Ripa, Laura; Reynaga, Esteban; Azcona-Gutiérrez, José Manuel; Rezusta, Antonio; Seral, Cristina; Antoñanzas, Fernando; Torres, Luis; López, Concepción; López-Cerero, Lorena; Cercenado, Emilia; et al.
Abstract: Background: Tetracycline resistance (Tet R ) is a marker of livestock-associated MRSA of lineage CC398. Objectives: To determine the MRSA CC398 prevalence among Tet R -MRSA recovered in Spanish hospitals located in regions with different pig-farming densities, and the influence of pig density as a key risk factor for its acquisition. Methods: Tet R -MRSA isolates ( n  =   232) recovered from clinical and epidemiological samples during January–June 2016 in 20 hospitals in 13 regions with different pig-farming densities were analysed. MRSA CC398 identification, detection of spa types, methicillin resistance genes and immune evasion cluster (IEC) genes were performed by PCR/sequencing. Statistical analyses were performed to establish the relationships between MRSA CC398 prevalence and pig density. Results: The global MRSA prevalence was 29.7% (6.9% Tet R -MRSA/MRSA), with 137 CC398 isolates recovered, representing 4.1% of total MRSA and 59.1% of Tet R -MRSA. Among MRSA CC398, 16 different spa types were recorded (t011: 72.3%), and all but two strains were IEC negative. Higher pig-density regions were associated with significant MRSA CC398 increases in hospitals located in adjacent regions ( P  < 0.001). Linear regression models explained the relationships between MRSA CC398 and pig density ( P  < 0.001), with an increase of 6.6 MRSA CC398 cases per 100 MRSA per increase of 100 pigs/km 2 in a region. Conclusions: High pig density leads to a significant increase in MRSA CC398 in hospitals in Spain, and its combination with a high human population could help its dissemination. In Spain, the prevalence of the zoonotic CC398 lineage is closely related to pig-farming density; therefore, specific tools could be implemented in order to detect its dissemination.